Evolving Research and Innovation Discourse in Indonesia: Insights From Topic Modelling and The Technology Innovation System - Shiddiq Sugiono; Reninta Dewi Nugraheni (National Research and Innovation Agency, Indonesia, 2026)
Indonesia continues to face fragmentation and weak coordination within its innovation system, as reflected in its relatively lower position in the Global Innovation Index. Addressing this issue requires a comprehensive mapping of the innovation system, in which media coverage may serve as a reflective arena for capturing the activities and interactions of innovation actors. This study aims to examine the condition of Indonesia’s innovation system following the establishment of National Research and Innovation Agency (BRIN) through the Technological Innovation System (TIS) framework based on media discourse analysis. The dataset consists of 2,975 news articles published between 2022 and 2024 from five of Indonesia’s most popular online news portals. The analysis employed Latent Dirichlet Allocation topic modeling, topic proportion analysis, and topic co-occurrence analysis. The findings identified 11 topics, with Industrial Policy and Economic Development emerging as the most dominant. Overall, the topic distribution aligns closely with Indonesia’s national development agenda for 2020–2024. Topic proportion analysis further indicates that national research and innovation discourse is increasingly oriented toward industrial development and environmentally sustainable energy, underscoring the urgency of mission-oriented innovation policies. Nevertheless, knowledge development and knowledge diffusion have yet to become central of innovation system.